A life-stage approach for understanding population retention in sparsely populated areas. (December 2020) - Dyrting, Sigurd; Taylor, Andrew; Shalley, Fiona
Abstract: Population growth in developed nations has become increasingly concentrated towards metropolitan areas. In Australia, around 80% of national growth derives from its largest 7 cities but in sparsely populated areas, recent growth tends towards stagnation or decline. For these regions, there are no studies which systematically analyse a key aspect for population growth - drivers for population retention. Our study engages a life-stage approach to the analysis of a large survey about migration motivations and drivers as they relate to the Northern Territory of Australia. The Territory and Me survey was conducted during 2019 with more than 5200 current and former residents participating. In this study, we applied odds ratios, binomial regression and correspondence analysis to demonstrate the most important demographic and socio-economic characteristics associated with retention rates and factors for staying or leaving. Motivations for leaving were explained largely by two factors, one strongly associated with age and the other influenced by relative levels of familial and financial responsibilities. Other results highlight the importance of overseas born residents for their high retention rates across all life-stages, home ownership and having children resident in the Northern Territory. These findings can inform policy initiatives to positively influence future retention of people in different life-stages and ultimately help address low population growth for sparsely populated areas. Highlights: The life-stage approach to modelling retention is unique. Retention rates increase in later life-stages and are very low for early-career residents. Home ownership and having children make people 'stick' in sparsely populated areas. Overseas born residents are significantly more likely to be retained in sparsely populated areas. Two clear factors associated with age and familial/ financial responsibilities explain motivations for leaving.